ANALISIS PERAN PELATIH PADUAN SUARA DALAM MENINGKATKAN KETERAMPILAN MENYANYI PESERTA PADUAN SUARA DI SMK - Wahyu Kartika; Aloysius Mering; Henny Sanulita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study was initiated by researcher’s concern towards students’ interest in joining extracurricular activity of choir and listening to the choir’s voices performed was still in poor harmonization category. This choir was like unwell-trained so that researcher was also interested in analyzing the role of choir’s coach in SMK Kristen Immanuel 2 Sungai Raya. The method of this study was descriptive method in qualitative study by using musicology approach. Data source of this study was obtained from observation result, interview to choir coach, choir participants, art and culture teacher, headmaster, teachers and students in SMK Kristen Immanuel 2 Sungai Raya and also documents of musical score. Based on the result of data analysis, there were nine roles that choir coach must have. They were a vocal trainer, a sight singer, an arranger and a composer, a manager, a leader, a supervisor, a pianist or accompanist, a musical director and a motivator. Whereas the singing competences that choir participants must have was appropriate vocal techniques. They were body languages, respiration, articulation, intonation, phrasering, vibration, resonance, improvisation and expression.  Key words: analysis of coach’ roles, choir, singing competences